إدارة نفايات المستشفيات الصلبة في مدينة اللاذقية - شاهين هيثم (Latakia University Journal -Engineering Sciences Series, 2019)
The problems of Hospital Waste Management in Lattakia City have been growing at an alarming rate, due to shortages of financial resources, lack of trained man power, lack of education and awareness about the environmental health problems associated with hospital waste disposal. The present study aims at studying the processes of collecting, storing and transporting hospital waste in Lattakia; it also investigates the rate of waste generation in the governmental, teaching, private hospitals. Four hospitals were chosen for this work. National Hospital (public), Al-Assad (teaching), Zahi-Azrak (military) and Al-Markazy (private).High values of Bed Occupancy Ratio and Average Length of Stay were recorded in Al- Assad Hospital 101%and 3.8 respectively ,while small values were recorded in Al-Markazy Hospital (14.4%,1.3). The research work took into account the amounts of medical waste accumulated from each section. The highest amount was established in genus – delivery section (2Kg/P/day in Al-Markazy Hospital) and the lowest amount was in internal section (0.22Kg/P/day in Military Hospital).The total generation rates were determined (kilogram per patient, per day) for the four hospitals as follows: 1.29;1.01;0.84;0.67Kg/p/day for Al-Markazy,Al-Assad,National and Military Hospitals respectively. Moreover the study compares the different methods used in treating hospital wastes and makes recommendation for the most suitable method for the City of Lattakia. تعاني عملية إدارة نفايات المستشفيات في مدينة اللاذقية من نقص في رؤوس الأموال الموظفة لهذا الغرض، نقص في الطاقم البشري المدرب، نقص في الوعي البيئي وجهل في مخاطر تداول النفايات الطبية.ومن أهمها عدم وجود المعالجة السليمة لنفايات المستشفيات هذه. يهدف البحث إلى دراسة عملية جمع وتخزين ونقل النفايات الطبية المطبقة في مستشفيات اللاذقية؛ فضلا عن تحديد معدّل تولد النفايات الطبية في المستشفيات الحكومية، التعليمية والخاصة. لقد تم اختيار أربعة مستشفيات لإنجاز البحث وهي:المستشفى الوطني(عام)، مستشفى الأسد(تعليمي)، زاهي أزرق(عسكري) والمركزي(خاص). وقد تم تحديد نسبة انشغال الأسرة ومدة البقاء في المستشفيات المدروسة فكانت أعلى قيمة لنسبة الانشغال (101%) في مستشفى الأسد ، بينما بلغت فقط( 14.4%) في المستشفى المركزي. ثم حددت كميات النفايات الطبية لكل قسم من أقسام المستشفيات الأربع المدروسة ، وقد بلغت أعلى قيمة في قسم التوليد والنسائية (Kg/p/day2 في المستشفى المركزي) ولم تزد عن (Kg/P/day 0.22 في قسم الداخلية المستشفى العسكري). ومن خلال القيم المحسوبة للأقسام تم تحديد المعدل الوسطي لكل مستشفى فكانت 1.29؛1.01؛0.84 ؛0.67 كغ/مريض/يوم للمستشفى المركزي، مستشفى الأسد، المستشفى الوطني ثم العسكري على التوالي .كما جرت مقارنة بين طرق معالجة نفايات المستشفيات واقتراح الطريقة الملائمة لمعالجة نفايات المستشفيات في مدينة اللاذقية.